Development of a Vision-Based Mobile Robot Navigation System for Golf Balls Detection and Location - Mat Jusoh, Rizal (2007)
A significant challenge in the design of an autonomous mobile robot is the reliable detection of targets, obstacles and targets tracking. Many types of sensor are used for that purposes such as infrared, sonar, vision sensor and laser. Monocular vision is one of the methods used due to simplicity and computational cost compared to stereo vision. Based on current trends the autonomous mobile robot development, vision sensor is used as different functions such as target recognition, obstacles avoidance, and navigation.